Intracellular Ca2+ Stores and Ca2+ Influx Are Both Required for BDNF to Rapidly Increase Quantal Vesicular Transmitter Release - Michelle D. Amaral; Lucas Pozzo-Miller (Neural Plasticity)
Brain-derived neurotrophic factor (BDNF) is well known as a survival factor during brain development as well as a regulator of adult synaptic plasticity. One potential mechanism to initiate BDNF actions is through its modulation of quantal presynaptic transmitter release. In response to local BDNF application to CA1 pyramidal neurons, the frequency of miniature excitatory postsynaptic currents (mEPSC) increased significantly within 30 seconds; mEPSC amplitude and kinetics were unchanged. This effect was mediated via TrkB receptor activation and required both full intracellular Ca2+ stores as well as extracellular Ca2+. Consistent with a role of Ca2+-permeable plasma membrane channels of the TRPC family, the inhibitor SKF96365 prevented the BDNF-induced increase in mEPSC frequency. Furthermore, labeling presynaptic terminals with amphipathic styryl dyes and then monitoring their post-BDNF destaining in slice cultures by multiphoton excitation microscopy revealed that the increase in frequency of mEPSCs reflects vesicular fusion events. Indeed, BDNF application to CA3-CA1 synapses in TTX rapidly enhanced FM1-43 or FM2-10 destaining with a time course that paralleled the phase of increased mEPSC frequency. We conclude that BDNF increases mEPSC frequency by boosting vesicular fusion through a presynaptic, Ca2+-dependent mechanism involving TrkB receptors, Ca2+ stores, and TRPC channels.